The Effect of Task Based Learning Method on Students’ Writing Advertisement Text at Eightgrade of SMPN 1 Badiri in 2022/2023 Academic Year - Asriani Hasibuan; Gabby Maureen Pricilia; Derlina Sari Rambe; Sri Rahayu Silalahi (National Conference on Language, Education, and Technology Proceeding, 2023)
The purposes of this research are to find out: 1) the extent of using task-based learningmethod in teaching writing advertisement text at the eighthgrade students of SMPNegeri1 Badiri. 2) the extent of the students’ writing advertisement text before and afterusing task-based learning method on students’ writing advertisement text ability at theeighthgrade students of SMP Negeri 1 Badiri. 3) whether there is a significant effect ofusing task-based learning method on students’ writing advertisement text ability at theeighthgrade students of SMP Negeri 1 Badiri. The population of this research were all theeighthgrade students of SMP Negeri 1 Badiri totaling 242 students. The sample was theclass VIII4 students, which consist of 32 students who were taken by purposive sampling.The data collected by using observation sheet and test. The results of this research: 1)The use of task-based learning method was 3.6, it was categorized “very good”. 2) Themean score of the students’ writing advertisement text ability before using task-basedlearning method was 54.12, it was categorized “bad”. Meanwhile, after using task-basedlearning method was 85.4 it was categorized “very good”. 3) the results of data analysisshowed that the ttest is higher than ttable (ttest 15.52> ttable 2.04). The hypothesis wasaccepted. It means that there is a significant effect of tas-based learning method onstudents’ writing advertisement text ability at the eighth grade of SMP Negeri1 Badiri in2022/2023 academic year